Double Infections of the Invasive Ladybird Harmonia axyridis - de Groot, Michiel D.; Haelewaters, Danny (Frontiers in Ecology and Evolution, 2022)
The dramatic spread of invasive alien species over the past century is considered to be an important threat to ecosystems worldwide. The harlequin ladybird, Harmonia axyridis, from eastern Asia, is considered to be one of the most invasive species. Originally introduced across the world as a biological control agent against crop pests owing to its voracious appetite and hardiness, those same qualities have made H. axyridis an invader that is difficult to eradicate. Harmonia axyridis has proven resilient against a variety of pathogens that have negative effects on other coccinellids. However, little research has examined the effects of simultaneous infections of multiple natural enemies on H. axyridis. Here we present the available information on such double infections on H. axyridis, and discuss further research directions in this area.